(3GdhSjdI eNJUQ GdeYhfIs - (3TgGH GdOjf GHf GdgGFe CMeO Hf eMeOs; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3aEf cJGHi GdehVhY ai UfGYI GdghCi GdeSei HGdeYhfI deG cKQ Ydeg QCjJ Cf GbJUQ ai GOGb bdjdg Ydi ebGUOg s
(3BNQgG (B:s
(3hai gPG GdbOQ GdPi ChQOJg caGjI def YQag hef CQGO GdHUQ aYdjg HGdehYhfI s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdQjGVjGJs